Length Polymorphisms in Heme Oxygenase-1 and AKI after Cardiac Surgery - Leaf, David E. (J Am Soc Nephrol, 2016)
Heme oxygenase-1 (HO-1) catalyzes the degradation of heme, which may be involved in the pathogenesis of AKI. Length polymorphisms in the number of GT dinucleotide repeats in the HO-1 gene (HMOX1) promoter inversely associate with HMOX1 mRNA expression. We analyzed the association between allelic frequencies of GT repeats in the HMOX1 gene promoter and postoperative AKI in 2377 white patients who underwent cardiac surgery with cardiopulmonary bypass. We categorized patients as having the short allele (S; <27 GT repeats) or long allele (L; ≥27 GT repeats), and defined AKI as an increase in serum creatinine ≥0.3 mg/dl within 48 hours or ≥50% within 5 days, or the need for RRT. Compared with patients with the SS genotype, patients with the LL genotype had 1.58-fold (95% confidence interval, 1.06 to 2.34; P=0.02) higher odds of AKI. After adjusting for baseline and operative characteristics, the odds ratio for AKI per L allele was 1.26 (95% confidence interval, 1.05 to 1.50; P=0.01). In conclusion, longer GT repeats in the HMOX1 gene promoter associate with increased risk of AKI after cardiac surgery, consistent with heme toxicity as a pathogenic feature of cardiac surgery-associated AKI, and with HO-1 as a potential therapeutic target.